Pendampingan Penyusunan Modul Ajar Berbasis Pembelajaran Mendalam Bagi Guru Madrasah Ibtidaiyah - Ersila Devy Rinjani; Fitria Martanti; Ana Quthratun Nada; Ummu Jauharin Farda; Ma'as Shobirin; Gadis Herningtyasari; Linda Indiyarti Putri; Aris Abdul Ghoni; Muhammad Hasan Istamar; Sa'addudin An Nasih (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This service activity was motivated by the finding that most teachers did not understand the concept of deep learning, so the teaching modules used were still conventional, focused on text delivery, and minimally used interactive digital elements. This condition has an impact on the lack of optimal learning activities that should encourage high-level thinking skills. This service aims to assist teachers in developing deep learning-based teaching modules that are more meaningful and relevant to the Independent Curriculum. The method used is Participatory Rural Appraisal (PRA) through the active involvement of teachers in each stage of activities. The results of the service showed a significant 79 percent increase among the 108 teachers who participated in the service activities. The improvement is evident in the teacher's understanding of deep learning and their ability to develop teaching modules based on this concept.